Polishing pad, method for preparing polishing pad, and method for manufacturing semiconductor device
By adjusting the concentration of zinc, iron and aluminum and the total oxidation capacity index in the polishing pad, the problems of low polishing speed and frequent defects in semiconductor device manufacturing are solved, and a high-efficiency and low-defect polishing effect is achieved.
Patent Information
- Application Number
- CN202210479762.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-07
- Filing Date
- 2022-05-05
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2042-05-05
AI Technical Summary
During the manufacturing process of existing semiconductor devices, the hardness and electrical characteristics of the polishing pads in the CMP process are difficult to adjust, resulting in low polishing speed, frequent defects, and low process efficiency.
Using a polishing layer containing zinc, iron and aluminum, by adjusting the concentration and total oxidation capacity index of these metals, a polishing pad with excellent proper hardness and electrical characteristics is prepared to increase the polishing speed and reduce defect occurrence.
The polishing rate is improved and the defect is minimized, the polishing flatness and process efficiency of semiconductor devices are improved, and the appropriateness of the electrical characteristics of the polishing surface is ensured.
Smart Images

Figure CN115302402B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polishing pad used in a chemical mechanical planarization process of a semiconductor device, a method for preparing the polishing pad, and a method for manufacturing a semiconductor device using the polishing pad. Background Art
[0002] Chemical Mechanical Planarization (CMP) or Chemical Mechanical Polishing (CMP) can be used for various purposes in various technical fields. The CMP process is performed on the specified polishing surface of the polishing object and can be used to flatten the polishing surface, remove agglomerated substances, solve lattice damage, remove scratches and contamination sources, etc.
[0003] The CMP process technology of semiconductor processes can be classified according to the quality of the film to be polished or the shape of the surface after polishing. For example, it can be classified into single crystal silicon (single silicon) or polycrystalline silicon (polysilicon) according to the quality of the film to be polished, and can also be classified into various oxide films or metal film CMP processes such as tungsten (W), copper (Cu), aluminum (Al), ruthenium (Ru), tantalum (Ta) according to the type of impurities. In addition, it can also be classified into processes for improving the roughness of the substrate surface, processes for flattening the step difference caused by multi-layer circuit wiring, and device separation processes for selectively forming circuit wiring after polishing according to the shape of the surface after polishing.
[0004] The CMP process can be applied multiple times in the manufacturing process of semiconductor devices. Semiconductor devices include multiple layers, and each layer includes a complex and fine circuit pattern. In addition, in recent semiconductor devices, the size of a single chip is reduced, and the pattern of each layer is evolving in a more complex and fine direction. Therefore, in the preparation process of semiconductor devices, the purpose of the CMP process has been expanded to include not only the flattening of circuit wiring, but also the separation of circuit wiring and the improvement of wiring surface, etc., and as a result, more precise and reliable CMP performance is being required.
[0005] The polishing pad used in the CMP process is a process component that processes the polished surface to a desired level by friction, and is considered one of the most important factors in terms of thickness uniformity of the polished object after polishing, flatness of the polished surface, polishing quality, etc. Summary of the invention
[0006] Problem that the invention aims to solve
[0007] One embodiment provides a polishing pad having appropriate hardness, tensile strength, elongation, etc. One embodiment provides a polishing pad that appropriately adjusts the electrical properties of the polishing pad and the degree of adsorption between the polishing pad and the slurry during the polishing process based on the above properties, thereby improving the polishing speed and preventing defects.
[0008] Another embodiment provides a method for preparing a polishing pad having high process efficiency in polishing a semiconductor substrate.
[0009] Yet another embodiment provides a method for manufacturing a semiconductor device, in which the polishing pad of one embodiment is used when polishing the polished surface of the semiconductor substrate, thereby achieving a high polishing rate and suppressing defects to a minimum level compared to a case where a conventional polishing pad is used.
[0010] Means used to solve problems
[0011] A polishing pad according to an embodiment includes a polishing layer, wherein the polishing layer contains zinc, and a concentration of the zinc is 0.5 ppm to 40 ppm by weight based on a total weight of the polishing layer.
[0012] In one embodiment, the polishing layer further includes iron. Based on the total weight of the polishing layer, the concentration of the iron may be 1 ppm to 50 ppm by weight.
[0013] In one embodiment, the polishing layer further includes aluminum. Based on the total weight of the polishing layer, the concentration of the aluminum may be 2 ppm to 50 ppm by weight.
[0014] In one embodiment, the total oxidation ability index of the polishing layer represented by the following formula 3 may be 1.5 to 10,
[0015] Form 3:
[0016] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0017] Among them, the Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe Is the ppm concentration value of iron weight based on the total weight of the polishing layer, the Oxi. Alis the ionization index of the aluminum, which is the reciprocal of the primary ionization energy of the aluminum divided by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, the Oxi. Zn is the ionization index of zinc, which is the reciprocal of the primary ionization energy of zinc divided by the reciprocal of the primary ionization energy of aluminum, the reciprocal of the primary ionization energy of zinc, and the sum of the reciprocal of the primary ionization energy of iron, the Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0018] In one embodiment, based on the total weight of the polishing layer, the total concentration of the iron, zinc, and aluminum from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness may be 8 ppm to 30 ppm by weight.
[0019] In one embodiment, the hardness of the polishing layer is 53 to 60 Shore D, and the elongation of the polishing layer may be 80 to 110%.
[0020] A method for preparing a polishing pad of one embodiment may include the following steps: preparing a preliminary composition comprising a prepolymer; mixing zinc into the preliminary composition; preparing a composition for preparing a polishing layer comprising the preliminary composition, a foaming agent, and a curing agent; and preparing a polishing layer by curing the composition for preparing a polishing layer, wherein the concentration of zinc in the polishing layer is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer.
[0021] In one embodiment, the prepolymer includes an isocyanate compound, and the isocyanate compound includes any one of an aromatic diisocyanate compound and an alicyclic diisocyanate compound. The content of the isocyanate group in the prepolymer may be 6 wt % to 12 wt %.
[0022] A method for manufacturing a semiconductor device according to an embodiment includes: providing a polishing pad including a polishing layer, and bringing a polishing surface of the polishing layer into contact with a polished surface of a polishing object, and then relatively rotating the polishing layer and the polishing object to polish the polishing object; the polishing object includes a semiconductor substrate, and the polishing layer includes zinc, and the concentration of the zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer.
[0023] In one embodiment, the concentrations of the zinc, the iron, and the aluminum may be measured by inductively coupled plasma optical emission spectroscopy (ICP-OES).
[0024] In one embodiment, nitric acid and hydrochloric acid at pH 3 or below may be used to dissolve about 1 g of the polishing layer to prepare a polishing layer solution, and then the polishing layer solution is pretreated at a temperature of 200° C. for about 16 hours, and then the concentrations of zinc, iron, and aluminum are measured by an inductively coupled plasma emission spectrometer. For the concentrations of zinc, iron, and aluminum, the average value obtained after 5 measurements using the above method may be defined as the concentration value based on the total weight of the polishing layer.
[0025] In one embodiment, the concentration of zinc may be 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, the concentration of iron may be 1 ppm to 50 ppm by weight based on the total weight of the polishing layer, and the concentration of aluminum may be 2 ppm to 50 ppm by weight based on the total weight of the polishing layer.
[0026] A polishing pad according to an embodiment of the present invention comprises: a polishing layer, wherein the polishing layer comprises zinc, wherein the concentration of the zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, and the total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10,
[0027] Form 3:
[0028] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0029] In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer,
[0030] Said Oxi. Alis the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0031] Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0032] Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0033] A method for preparing a polishing pad according to an embodiment of the present invention comprises the following steps: preparing a preliminary composition comprising a prepolymer; mixing zinc into the preliminary composition; preparing a composition for preparing a polishing layer comprising the preliminary composition, a foaming agent and a curing agent; and preparing a polishing layer by curing the composition for preparing a polishing layer, wherein the concentration of zinc in the polishing layer is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, and the total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10,
[0034] Form 3:
[0035] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0036] In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer,
[0037] Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0038] Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0039] Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0040] A method for preparing a semiconductor device according to an embodiment of the present invention comprises the following steps: providing a polishing pad including a polishing layer, bringing a polishing surface of the polishing layer into contact with a polished surface of a polishing object, and then relatively rotating the polishing layer and the polishing object to polish the polishing object; the polishing object comprises a semiconductor substrate, the polishing layer comprises zinc, the concentration of the zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, and the total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10,
[0041] Form 3:
[0042] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0043] In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer,
[0044] Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0045] Said Oxi. Znis the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0046] Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0047] A polishing pad according to an embodiment includes: a polishing layer, wherein the polishing layer includes zinc, wherein the concentration of the zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, wherein the total concentration of iron, zinc, and aluminum contained in the polishing layer from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness is 8 ppm to 30 ppm by weight based on the total weight of the polishing layer, and wherein the total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10,
[0048] Form 3:
[0049] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0050] In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer,
[0051] Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0052] Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0053] Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0054] A method for preparing a polishing pad according to an embodiment of the present invention comprises the following steps: preparing a preliminary composition including a prepolymer; mixing zinc into the preliminary composition; preparing a composition for preparing a polishing layer including the preliminary composition, a foaming agent and a curing agent; and preparing a polishing layer by curing the composition for preparing a polishing layer, wherein the concentration of zinc in the polishing layer is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, the total concentration of iron, zinc and aluminum contained in the polishing layer from the polishing surface of the polishing layer to a depth of 1 / 2 of the total thickness is 8 ppm to 30 ppm by weight based on the total weight of the polishing layer, and the total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10,
[0055] Form 3:
[0056] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0057] In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer,
[0058] Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0059] Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0060] Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0061] A method for preparing a semiconductor device according to an embodiment of the present invention comprises the following steps: providing a polishing pad including a polishing layer, bringing a polishing surface of the polishing layer into contact with a polished surface of a polishing object, and then relatively rotating the polishing layer and the polishing object to polish the polishing object; the polishing object comprises a semiconductor substrate, the polishing layer comprises zinc, the concentration of the zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, the total concentration of iron, the zinc and aluminum contained in the polishing layer from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness is 8 ppm to 30 ppm by weight based on the total weight of the polishing layer, the total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10,
[0062] Form 3:
[0063] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0064] In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer,
[0065] Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0066] Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0067] Said Oxi.Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0068] Effects of the Invention
[0069] Since the polishing pad includes a polishing layer containing respective metals corresponding to the metal concentration in the processing composition treating the polishing pad under prescribed conditions, the polishing surface of the polishing layer can exhibit appropriate hardness and electrical characteristics.
[0070] Thus, the polishing pad can present a polishing rate and polishing flatness within a target range when polishing the polishing object. In addition, since the polishing pad contains the metal in an appropriate content, the degree of adsorption of the polishing pad to the slurry is increased during the polishing process, and the polishing pad can have an improved polishing rate and polishing performance.
[0071] The method for manufacturing a semiconductor device using the polishing pad has high process efficiency in polishing a semiconductor substrate as a polishing object. In addition, the method for manufacturing a semiconductor device of an embodiment can make the polished surface of the semiconductor substrate have high polishing flatness and minimal defects.
[0072] In addition, since the polishing pad of the embodiment contains the metal component, the electrical characteristics of the polishing surface can be appropriately adjusted. For example, since the polishing layer contains the metal component, the surface-modified polishing particles can be easily bonded to the polishing surface by electrostatic attraction.
[0073] In particular, the surface potential of the polishing surface can be adjusted according to the metal component, so that the polishing particles with surface modification are bound to the polishing surface by appropriate attraction.
[0074] Since the metal component has the total oxidation ability index as described above, the surface-modified polishing particles can be bonded to the polishing surface through appropriate electrostatic attraction.
[0075] Therefore, a proper amount of polishing particles can remain near the polishing surface under the action of appropriate bonding force. Therefore, a semiconductor substrate such as a semiconductor wafer can be effectively polished by the polishing surface and the polishing particles. BRIEF DESCRIPTION OF THE DRAWINGS
[0076] Figure 1A and Figure 1B A cross section of the polishing pad according to one embodiment is schematically shown.
[0077] Figure 2The process diagram schematically shows a method for manufacturing a semiconductor device according to an embodiment.
[0078] Description of Reference Numerals
[0079] 100, 110, 200: polishing pad
[0080] 10: Polishing layer
[0081] 11: First surface
[0082] 12: Second Surface
[0083] 13: Groove
[0084] 20: Buffer layer
[0085] 30: First bonding layer
[0086] 40: Second adhesive layer
[0087] 120: Tablet
[0088] 130: Semiconductor substrate
[0089] 140: Supply nozzle
[0090] 150: Polishing slurry
[0091] 160: Polishing head
[0092] 170: Dresser DETAILED DESCRIPTION
[0093] According to the following examples, the advantages, features and implementation methods of the present invention will be more clearly understood. However, the present invention is not limited to the following exemplary embodiments, but can be implemented in various forms, which are provided only to make the present invention more complete and fully provide the scope of the present invention to ordinary technicians in the field to which the present invention belongs, and the present invention will be defined by the appended claims.
[0094] In order to clearly express each layer and region in the figure, the thickness is enlarged and shown. And in the accompanying drawings, for the convenience of explanation, the thickness of some layers and regions is exaggerated. Throughout the specification, the same reference numerals represent the same constituent elements.
[0095] In addition, in this specification, when a part of a layer, film, region, plate, etc. is referred to as being "above" or "over" another part, this includes not only the case where it is directly "above" another part, but also the case where there are other parts in the middle. On the contrary, when a part is referred to as being directly "above" another part, it means that there are no other parts in the middle. At the same time, when a part of a layer, film, region, plate, etc. is referred to as being "below" or "under" another part, this includes not only the case where it is directly "under" another part, but also the case where there are other parts in the middle. On the contrary, when a part is referred to as being directly "under" another part, it means that there are no other parts in the middle.
[0096] In one embodiment, a polishing pad is provided, comprising a polishing layer, wherein the polishing layer contains zinc, and the concentration of the zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer.
[0097] With the high integration of semiconductor devices in recent years, the polishing pad, as a process equipment used in the manufacturing process of semiconductor devices, is one of the elements that require precise process control. The polishing pad includes a polishing layer that directly transmits the polishing effect to the polishing object, and the composition and physical properties of the polishing layer are factors that directly affect the polishing quality and polishing results of the polishing object. In the polishing pad of one embodiment, the polishing layer contains zinc, and the polishing effect on the polishing object can be optimized by using a polishing layer with a zinc concentration of 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer.
[0098] Figure 1A and Figure 1B Schematically shows a cross section of the polishing pad according to an embodiment. Figure 1A The polishing pad 100 includes the polishing layer 10, and may include a buffer layer 20 on one surface of the polishing layer 10. The polishing layer 10 is in the form of a sheet with a specified thickness, and includes: a first surface 11, which functions as a polishing surface that directly or indirectly contacts the polished surface of the polishing object; and a second surface 12, which is the opposite surface of the first surface 11.
[0099] In one embodiment, the thickness of the buffer layer 20 may be about 0.5 mm to about 2.5 mm, for example, about 0.8 mm to about 2.5 mm, for example, about 1.0 mm to about 2.5 mm, for example, about 1.0 mm to about 2.0 mm, for example, about 1.2 mm to about 1.8 mm.
[0100] Reference Figure 1BIn one embodiment, the polishing pad 200 may include the polishing layer 10 and the buffer layer 20, and may further include a first adhesive layer 30 disposed at an interface between the polishing layer 10 and the buffer layer 20. For example, the first adhesive layer 30 may be derived from a heat-sealing adhesive, but is not limited thereto.
[0101] The polishing pad 200 may further include a second adhesive layer 40 disposed on the second surface 12 of the polishing layer 10. The second adhesive layer 40 is a structure for adhering the polishing pad to a plate of a polishing device, and may be disposed directly above the second surface 12 of the polishing layer 10, or may be disposed as shown in FIG. Figure 1B As shown, the second adhesive layer 40 is disposed on other layers such as the buffer layer 20 on the polishing layer 10. For example, the second adhesive layer 40 may be derived from a pressure sensitive adhesive, but is not limited thereto.
[0102] The buffer layer 20 is disposed on the second surface 12 of the polishing layer 10 to support the polishing layer 10 and relieve the external pressure or impact transmitted to the polished surface during the polishing process. Thus, in the polishing process using the polishing pad 100, it helps to prevent the polishing object from being damaged or defective.
[0103] In one embodiment, the polishing pad may include a through region that penetrates the uppermost layer and the lowermost layer thereof. The through region is used as a structure for detecting a polishing end point during use of the polishing pad, and light having a specified wavelength condition can pass through the through region. In one embodiment, a light transmission window may be provided in the through region. The transmittance of the light transmission window to light of any wavelength from about 500 nm to about 700 nm may exceed about 30%, for example, may be about 40% to about 80%.
[0104] The polishing layer may include a cured product of a preliminary composition containing a urethane prepolymer. In one embodiment, the preliminary composition may also include a curing agent and a foaming agent. The "prepolymer" refers to a polymer with a relatively low molecular weight whose polymerization degree is interrupted in the intermediate stage for the convenience of molding when preparing a cured product. The prepolymer itself can be finally formed into a cured product through additional curing processes such as heating and / or pressurization, or mixed and reacted with other polymerizable compounds, such as additional compounds such as different types of monomers or different types of prepolymers, to finally form a cured product.
[0105] In one embodiment, the urethane-based prepolymer may be prepared by reacting an isocyanate compound with a polyol compound.
[0106] The isocyanate compound used in preparing the urethane prepolymer may be one selected from the group consisting of aromatic diisocyanate, aliphatic diisocyanate, alicyclic diisocyanate and a combination thereof. In one embodiment, the isocyanate compound may include aromatic diisocyanate.
[0107] The isocyanate compound may include, for example, 2,4-toluenediisocyanate (2,4-TDI), 2,6-toluenediisocyanate (2,6-TDI), naphthalene-1,5-diisocyanate, p-phenylenediisocyanate, tolidinediisocyanate, 4,4'-diphenylmethanediisocyanate, hexamethylenediisocyanate, dicyclohexylmethanediisocyanate, 4,4'-dicyclohexylmethanediisocyanate, 12 One of the group consisting of MDI, isophorone diisocyanate and combinations thereof.
[0108] The "polyol" refers to a compound containing at least two hydroxyl groups (-OH) per molecule. In one embodiment, the polyol compound may include a diol compound containing two hydroxyl groups, that is, diol or glycol.
[0109] The polyol compound may include, for example, one selected from the group consisting of polyether polyol, polyester polyol, polycarbonate polyol, acryl polyol, and combinations thereof.
[0110] The polyol compound, for example, may include one selected from the group consisting of polytetramethylene ether glycol (PTMG), polypropylene ether glycol, ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,2-butylene glycol, 1,3-butylene glycol, 2-methyl-1,3-propylene glycol, 1,4-butylene glycol, neopentyl glycol, 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, diethylene glycol (DEG), dipropylene glycol (DPG), tripropylene glycol, polypropylene glycol, and combinations thereof.
[0111] The polyol compound can have a weight average molecular weight (Mw) of about 100 g / mol to about 3000 g / mol. For example, the polyol can have a weight average molecular weight (Mw) of about 100 g / mol to about 3000 g / mol, for example, about 100 g / mol to about 2000 g / mol, for example, about 100 g / mol to about 1800 g / mol.
[0112] In one embodiment, the polyol compound may include a low molecular weight polyol having a weight average molecular weight (Mw) of about 100 g / mol or more and less than about 300 g / mol and a high molecular weight polyol having a weight average molecular weight (Mw) of about 300 g / mol or more and about 1800 g / mol or less. In one embodiment, the high molecular weight polyol may include a first high molecular weight polyol having a weight average molecular weight (Mw) of about 500 g / mol or more and about 800 g / mol or less; and a second high molecular weight polyol having a weight average molecular weight (Mw) of greater than about 800 g / mol and about 1800 g / mol or less. In this case, the polyol compound may form an appropriate cross-linked structure in the urethane prepolymer, and the polishing layer formed by curing the preliminary composition containing the urethane prepolymer under the prescribed process conditions may be more conducive to achieving the effect.
[0113] The urethane prepolymer may have a weight average molecular weight (Mw) of about 500 g / mol to about 3000 g / mol. The urethane prepolymer, for example, may have a weight average molecular weight (Mw) of about 600 g / mol to about 2000 g / mol, for example, about 800 g / mol to about 1000 g / mol. In the case where the urethane prepolymer has a degree of polymerization corresponding to the weight average molecular weight (Mw), the polishing layer formed by curing the preliminary composition under prescribed process conditions may be more conducive to having a chemical bonding structure for achieving the excellent polishing characteristics.
[0114] In one embodiment, the isocyanate compound used to prepare the urethane prepolymer may include an aromatic diisocyanate compound, and the aromatic diisocyanate compound may include, for example, 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI). In addition, the polyol compound used to prepare the urethane prepolymer may include, for example, polytetramethylene ether glycol (PTMG) and diethylene glycol (DEG).
[0115] In another embodiment, the isocyanate compound used to prepare the urethane prepolymer may include an aromatic diisocyanate compound and an alicyclic diisocyanate compound. For example, the aromatic diisocyanate compound includes 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI), and the alicyclic diisocyanate compound may include dicyclohexylmethane diisocyanate (DCI). 12 In addition, the polyol compound used to prepare the urethane prepolymer may include, for example, polytetramethylene ether glycol (PTMG) and diethylene glycol (DEG).
[0116] In the preliminary composition, the total amount of the polyol compound can be about 100 parts by weight to about 250 parts by weight, for example, about 120 parts by weight to about 250 parts by weight, for example, about 120 parts by weight to about 240 parts by weight, for example, about 150 parts by weight to about 240 parts by weight, for example, about 190 parts by weight to about 240 parts by weight, relative to 100 parts by weight of the total amount of the isocyanate compound in all the components used to prepare the urethane prepolymer.
[0117] In the preliminary composition, when the isocyanate compound used to prepare the urethane prepolymer includes the aromatic isocyanate compound, and the aromatic isocyanate compound includes 2,4-toluene diisocyanate (2,4-TDI) and 2,6-toluene diisocyanate (2,6-TDI), the content of 2,6-toluene diisocyanate (2,6-TDI) relative to 100 parts by weight of the 2,4-toluene diisocyanate (2,4-TDI) can be about 1 part by weight to about 40 parts by weight, for example, about 1 part by weight to about 30 parts by weight, for example, about 3 parts by weight to about 28 parts by weight, for example, about 1 part by weight to about 10 parts by weight.
[0118] In the preparatory composition, when the isocyanate compound used to prepare the urethane prepolymer includes the aromatic isocyanate compound and the alicyclic isocyanate compound, the content of the alicyclic isocyanate compound can be about 5 parts by weight to about 30 parts by weight, for example, about 10 parts by weight to about 25 parts by weight, relative to the total 100 parts by weight of the aromatic isocyanate compound. In the preparatory composition, the content of isocyanate groups (NCO%) can be about 6% by weight to about 12% by weight, for example, about 6% by weight to about 10% by weight, for example, about 6% by weight to about 9% by weight. The content of isocyanate groups refers to the weight percentage of isocyanate groups (-NCO) that do not undergo urethane reaction but exist as free reactive groups in the total weight of the preparatory composition. The isocyanate content (NCO%) of the preparatory composition can be designed by comprehensively adjusting the types and contents of the isocyanate compound and the polyol compound used to prepare the ethyl formate prepolymer, the temperature, pressure, time and other process conditions of the preparation process of the ethyl formate prepolymer, and the types and contents of the additives used in the preparation of the ethyl formate prepolymer.
[0119] The type of the additive may include one selected from the group consisting of a surfactant, a pH adjuster, an adhesive, an antioxidant, a heat stabilizer, a dispersion stabilizer, and a combination thereof. The names such as "surfactant" and "antioxidant" are arbitrarily designated based on the main function of the substance, and the functions of each of the substances are not limited to the functions designated by the names of the substances.
[0120] In the polishing pad of an embodiment, the polishing layer thereof contains zinc at the concentration and satisfies the structure and chemical composition, so that when the polishing pad is applied to the manufacturing process of a semiconductor device, the best polishing performance can be achieved. The chemical composition of the polishing layer interacts with the zinc at the specified concentration, so that the polishing surface of the polishing layer can exhibit suitable electrical characteristics in the polishing of a semiconductor substrate containing silicon (Si), copper (Cu) or tungsten (W).
[0121] The polishing layer may contain metal. The metal may be contained in the polishing layer in the form of metal particles, metal ions or metal salts. The metal salt may be a metal organic salt or a metal inorganic salt.
[0122] The oxidation number of the metal may be from +1 to +3. For example, the oxidation number of the metal may be from +2 to +3. Since the metal having the oxidation number is included, the polishing performance of the polishing layer can be significantly improved. Specifically, when the polishing layer includes the metal having the oxidation number as described above, an optimal potential condition for flatly polishing the semiconductor substrate at an appropriate level of polishing rate can be formed in a state where the polishing surface thereof is in contact with the semiconductor substrate as the polishing object.
[0123] Specifically, the metal may include one selected from the group consisting of zinc, iron, aluminum, and a combination thereof.
[0124] More specifically, the polishing layer may contain zinc. The zinc may be contained in the polishing layer in the form of an inorganic salt or an organic salt. For example, the oxidation number of the zinc may be +2.
[0125] The concentration of zinc in the polishing layer can be about 0.5 ppm to about 40 ppm by weight, for example, about 1 ppm to about 40 ppm by weight, for example, about 2 ppm to about 40 ppm by weight, for example, about 2 ppm to about 30 ppm by weight, based on the total weight of the polishing layer.
[0126] The polishing layer may further include iron. The iron may be included in the polishing layer in the form of an inorganic salt or an organic salt. In this case, the oxidation number of the iron may be +2. The oxidation number of the iron may be +3.
[0127] The concentration of iron in the polishing layer can be about 1 ppm to about 40 ppm by weight, for example, about 1 ppm to about 10 ppm by weight, for example, about 2 ppm to about 30 ppm by weight, for example, about 2 ppm to 20 ppm by weight, for example, about 4 ppm to about 40 ppm by weight, for example, about 4 ppm to about 20 ppm by weight, based on the total weight of the polishing layer.
[0128] The polishing layer may further include aluminum. The aluminum may be included in the polishing layer in the form of an inorganic salt or an organic salt. In this case, the oxidation number of the aluminum may be +3.
[0129] The concentration of aluminum in the polishing layer can be about 2 ppm to about 50 ppm by weight, for example, about 2 ppm to about 40 ppm by weight, for example, about 2 ppm to about 30 ppm by weight, for example, about 2 ppm to about 20 ppm by weight, for example, about 2 ppm to about 10 ppm by weight, for example, about 3 ppm to about 50 ppm by weight, for example, about 3 ppm to 40 ppm by weight, for example, about 3 ppm to about 30 ppm by weight, for example, about 3 ppm to about 10 ppm by weight, based on the total weight of the polishing layer.
[0130] The sum of the concentrations of the zinc, the iron, and the aluminum in the polishing layer can be about 5 ppm to about 40 ppm by weight, for example, about 7 ppm to about 35 ppm by weight, for example, about 5 ppm to about 30 ppm by weight, for example, about 8 ppm to 20 ppm by weight, for example, about 8 ppm to about 15 ppm by weight, for example, about 9 ppm to about 20 ppm by weight, for example, about 8 ppm to about 15 ppm by weight, based on the total weight of the polishing layer.
[0131] The concentration of the metal in the polishing layer can be measured by the following method.
[0132] The concentration of the metal in the polishing layer can be measured by ICP-OES.
[0133] The metal concentration in the polishing pad measured by the ICP-OES is a numerical average value obtained by measuring the polishing layer at least 5 times in the same way. For example, samples are taken at random positions of the polishing layer, and then the samples are dissolved by acid, and the mass of the metal contained in each sample is measured by the ICP-OES method, and then the concentration of the metal can be calculated based on the mass of each sample. The mass of the sample can be about 0.5 g to about 3 g. The mass of the sample can be about 1 g.
[0134] The polishing layer can be dissolved using nitric acid and hydrochloric acid, and the solution is pretreated at a temperature of about 200° C. for about 16 hours, and then the concentration of the metal is measured by ICP-OES. In addition, the metal concentration in the polishing layer can be uniform as a whole. For example, when the polishing layer is observed from the upper side, a plurality of 1 cm×1 cm square grids can be equally divided. The metal concentration in the grid can be uniform. The standard deviation of the metal concentration in the plurality of grids can be about 5 ppm or less. The standard deviation of the metal concentration in the plurality of grids can be about 4 ppm. The standard deviation of the metal concentration in the plurality of grids can be about 3 ppm.
[0135] For the concentration of each metal in this specification, the above method is used to perform 5 measurements, and the average value is defined as the concentration value based on the entire weight of the polishing layer.
[0136] In addition, the sample can be randomly taken from the polishing surface of the polishing layer to the 1 / 2 depth of the entire thickness. The sample from the polishing surface to the 1 / 2 depth can be measured by the ICP-OES, so that the metal concentration from the polishing surface to the 1 / 2 depth can be measured.
[0137] The concentration of each of zinc, iron and aluminum in the polishing layer may satisfy the above range within the entire thickness of the polishing layer. More specifically, the concentration of each of zinc, iron and aluminum in the polishing layer may satisfy the above range in the region from the polishing surface to 1 / 2 of the thickness of the polishing layer.
[0138] The total concentration of zinc, iron and aluminum in the polishing layer may satisfy the above range within the entire thickness of the polishing layer. More specifically, the total concentration of zinc, iron and aluminum in the polishing layer may satisfy the above range in the region from the polishing surface to 1 / 2 of the thickness of the polishing layer.
[0139] The concentration of each of zinc, iron and aluminum or their total concentration satisfies the range, particularly in the region from the polishing surface to a depth of 1 / 2 of the thickness of the polishing layer, thereby achieving the following effect: providing uniform polishing performance throughout the entire polishing process of polishing while cutting the surface with a dresser.
[0140] The zinc concentration in the polishing layer can be about 0.5 ppm to about 40 ppm by weight, for example, about 1 ppm to about 40 ppm by weight, for example, about 2 ppm to about 40 ppm by weight, for example, about 2 ppm to about 30 ppm by weight, based on the overall weight of the region from the polishing surface to a depth of 1 / 2 of the thickness of the polishing layer.
[0141] The iron concentration in the polishing layer can be about 1 ppm to about 40 ppm by weight, for example, about 1 ppm to about 10 ppm by weight, for example, about 2 ppm to about 30 ppm by weight, for example, about 2 ppm to 20 ppm by weight, for example, about 4 ppm to about 40 ppm by weight, for example, about 4 ppm to about 20 ppm by weight, based on the overall weight of the region from the polishing surface to a depth of 1 / 2 of the thickness of the polishing layer.
[0142] The concentration of aluminum in the polishing layer can be about 2 ppm to about 50 ppm by weight, for example, about 2 ppm to about 40 ppm by weight, for example, about 2 ppm to about 30 ppm by weight, for example, about 2 ppm to about 20 ppm by weight, for example, about 2 ppm to about 10 ppm by weight, for example, about 3 ppm to about 50 ppm by weight, for example, about 3 ppm to 40 ppm by weight, for example, about 3 ppm to about 30 ppm by weight, for example, about 3 ppm to about 10 ppm by weight, for example, about 3 ppm to about 50 ppm by weight, for example, about 3 ppm to 40 ppm by weight, for example, about 3 ppm to about 30 ppm by weight, for example, about 3 ppm to about 10 ppm by weight.
[0143] The total concentration of zinc, iron and aluminum in the polishing layer can be about 5 ppm to about 40 ppm by weight, for example, about 7 ppm to about 35 ppm by weight, for example, about 5 ppm to about 30 ppm by weight, for example, about 8 ppm to 20 ppm by weight, for example, about 8 ppm to about 15 ppm by weight, for example, about 9 ppm to about 20 ppm by weight, for example, about 8 ppm to about 15 ppm by weight, for example, about 9 ppm to about 20 ppm by weight, for example, about 8 ppm to about 15 ppm by weight.
[0144] In particular, the polishing layer can be cut by a trimmer or the like when polishing a semiconductor substrate. Therefore, in the polishing layer, the region that mainly contacts the semiconductor substrate can be from the polishing surface to a depth of about 1 / 2 of the thickness of the polishing layer. Therefore, when the metal concentration from the polishing surface to a depth of about 1 / 2 of the thickness of the polishing layer is within the range, the polishing pad of the embodiment can have improved performance.
[0145] Since the polishing layer contains the metal at an appropriate concentration, the polishing pad of the embodiment can have improved polishing performance. More specifically, since the polishing layer contains the iron, the aluminum, and the zinc at appropriate concentrations, respectively, it can have appropriate physical properties such as hardness and elongation. In addition, the metal can improve the degree of adsorption between the slurry used in chemical mechanical polishing and the polishing surface by adjusting the electrical properties of the polishing pad of the embodiment. As a result, the polishing pad of the embodiment can achieve polishing performance such as a polishing rate (RR) at a target level and a low level of defects.
[0146] More specifically, the polishing layer of an embodiment contains each of the zinc, iron and aluminum or a combination thereof at the above-mentioned concentrations, and at the same time, when the structure and chemical composition of the polishing layer meet the above-mentioned characteristics, when it is applied to the manufacturing process of a semiconductor device, the best polishing performance can be achieved. That is, the elements and molecular components generated by the chemical composition of the polishing layer interact with the appropriate concentrations of zinc, iron and aluminum, so that the polishing surface of the polishing layer can present physical and electrical properties suitable for polishing a semiconductor substrate containing silicon (Si), copper (Cu) or tungsten (W).
[0147] For example, when the concentration of zinc in the polishing layer is within the range and the total concentration of the metal in the polishing layer satisfies the range, the polishing layer can have appropriate hardness and elongation. In addition, since the polishing layer contains the metal at an appropriate concentration, the adsorption characteristics of the polishing surface and the polishing particles contained in the slurry can be appropriately improved. As a result, the polishing pad of the embodiment can achieve the desired polishing rate and defect reduction effect.
[0148] When the concentration of zinc in the polishing layer satisfies the above range and the concentrations of iron and aluminum satisfy the above range, the polishing layer can have appropriate hardness and elongation due to the appropriate metal concentration. In addition, since the polishing layer has an appropriate metal concentration, it can have appropriate electrical properties and appropriate adsorption and desorption properties with the slurry. As a result, the polishing pad of the embodiment can achieve the desired polishing rate and defect reduction effect.
[0149] As described above, in the polishing layer, the sum of the concentrations of the iron, the zinc, and the aluminum at a depth of 1 / 2 of the entire thickness from the polishing surface thereof may be within the range.
[0150] When the sum of the iron, zinc, and aluminum concentrations is out of the range and too low, the hardness of the polishing layer is reduced to be out of the normal range, and it may be difficult to achieve a desired polishing rate. On the contrary, when the sum of the iron, zinc, and aluminum concentrations is out of the range and too high, the hardness of the polishing layer is increased to be out of the normal range, and there is a risk that defects such as scratches on the surface of the semiconductor substrate or the like to be polished will increase.
[0151] On the one hand, during the polishing process, the metal in the polishing layer can be physically or chemically bonded to the slurry applied to the polishing surface. The polishing pad of one embodiment satisfies that the sum of the concentrations of the iron, zinc and aluminum in the polishing layer is within an appropriate range, so that it can have an improved polishing rate, polishing flatness and defect reduction effect in terms of physical or chemical bonding with the slurry components. At this time, the physical or chemical bonding may include one selected from the group consisting of electrical bonding, covalent bonding, ionic bonding, coordination bonding, van der Waals force, electrostatic repulsion, hydrogen bonding and combinations thereof, but is not limited thereto. That is, in the polishing layer, when the sum of the concentrations of the iron, zinc and aluminum deviates from the range and is too high or too low, the physical or chemical bonding force with the components in the slurry becomes too high or too low, so there is a hidden danger that it is difficult to ensure an appropriate level of adsorption and desorption force between each other. If the adhesion of the components in the slurry is too high and desorption is difficult to occur, there is a risk of scratches on the surface of the semiconductor substrate to be polished. If the adhesion of the components in the slurry is too low, it may be difficult to achieve the target level of polishing rate.
[0152] In one embodiment, the polishing layer may have a total oxidation capacity index represented by the following Formula 2 or Formula 3. The total oxidation capacity index of the polishing layer may be about 1.5 to about 10.
[0153] In order to calculate the total oxidizing capacity index, the ionization index (Oxi. x ),
[0154] Type 1:
[0155]
[0156] Wherein, the x is a metal contained in the polishing layer. The x can be a metal contained in the polishing layer in a significant content.
[0157] The x may be the zinc, the iron or the aluminum.
[0158] The Ex is the primary ionization energy of the x metal.
[0159] The Σ(1 / Ex) is the sum of the reciprocals of the primary ionization energies of the metals contained in the polishing layer.
[0160] The ionization index may be an index indicating the possibility of physical or chemical bonding, for example, ionic bonding or electrical bonding, between the metal contained in the polishing layer and the polishing particles contained in the slurry. In addition, the ionization index of the metal in the polishing layer may have a strong influence on the physical and chemical bonding between the polishing pad and the slurry.
[0161] Specifically, the zinc, iron and aluminum are metals with ionization energy and can be organically / inorganically combined with the components of the slurry. The ionization energy is the energy required to remove electrons from atoms or molecules. The greater the ionization energy, the more difficult it is to remove electrons, and the smaller the ionization energy, the more likely it is to become a cation, and therefore the more reactive it is.
[0162] Thus, in order to calculate the relative proportion of the ionization degree of the zinc, the iron and the aluminum in the polishing pad, the ionization index expressed in the form of an index is obtained by taking the reciprocal of the primary ionization energy of the zinc, the iron and the aluminum and dividing it by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc and the reciprocal of the primary ionization energy of the iron. That is, for each metal in the polishing layer, the larger its ionization index is, the greater its reactivity with the slurry components is, and conversely, the smaller its ionization index is, the less reactivity with the slurry components tends to be. Therefore, the ionization index of each of the metals can be used as an indicator of the physical or chemical bonding force of the components in the slurry related to the reactivity of each of the metals, and can be used as a factor constituting an oxidation ability index, wherein the oxidation ability index has a specified numerical range and is related to the polishing performance of the polishing pad, and represents the technical significance of achieving the best performance. The total oxidation ability index can be expressed by the following formula 2.
[0163] For example, the total oxidation ability index is a value obtained by multiplying the ionization index of the x metal by the concentration (ppm) value of the x metal and taking the sum of the products of the respective ionization indices and the concentration (ppm) values. As for the factors constituting the total oxidation ability index, the concentration of the x metal is a value having a ppm unit derived by ICP-OES as described above, or, as a factor constituting the oxidation ability index, only its numerical value is applied. In addition, the ionization index of the x metal itself is a value without a unit. Therefore, the oxidation ability index defined by the sum of the concentration of the x metal and the ionization index value of the x metal is shown as an index without a unit.
[0164] Formula 2:
[0165] Total oxidation capacity index = ∑(Con. x ×Oxi. x )
[0166] Among them, Con. x is the ppm concentration value of the x metal weight based on the total weight of the polishing layer.
[0167] For example, the metal may be the zinc, the iron, and the aluminum.
[0168] For example, the total oxidizing capacity index can be expressed by the following formula 3:
[0169] Form 3:
[0170] Total oxidizing capacity index = (Con. Al ×Oxi. Al )+(Con. Zn ×Oxi. Zn )+(Con. Fe ×Oxi. Fe )
[0171] in,
[0172] The Con. Al is the ppm concentration value of the aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of the zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm of the iron weight based on the total weight of the polishing layer,
[0173] Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0174] Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron,
[0175] Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
[0176] The total oxidizing capacity index may be from about 2 to about 9, for example, from about 2 to about 8, for example, from about 3 to about 7, for example, from about 2 to about 7.
[0177] The total oxidation capacity index may be a degree of bonding between the polishing layer and the polishing particles contained in the slurry caused by the metal contained in the polishing layer. For example, the total oxidation capacity index may represent the strength of bonding between the polishing layer and the polishing particles contained in the slurry through the zinc, the iron, and the aluminum.
[0178] For example, the total oxidation capacity index may be a value that represents the electrical properties of the polishing layer in the form of an index. That is, a polishing pad having a polishing layer with an appropriate total oxidation capacity index may allow the polishing particles contained in the slurry to be easily physically or chemically bonded to the polished surface. When the total oxidation capacity index is within a certain range, it is ensured that the polishing layer has an appropriate level of polarity, and therefore, the polished surface may have an appropriate charge. Therefore, the repulsive force caused by the electrostatic repulsion between the polishing surface and the polishing particles contained in the slurry may be reduced. As a result, the polishing pad of the embodiment may substantially improve the polishing participation of the polishing particles contained in the slurry, and may have an improved polishing rate.
[0179] In addition, due to the appropriate total oxidation capacity index, the polishing layer and the polishing particles contained in the slurry can interact appropriately during the polishing process. Therefore, the polishing particles contained in the slurry are easily adsorbed on the polishing pad, so that the polishing rate is increased and the polishing particles contained in the slurry are easily desorbed from the polished surface, so that the defects on the polished wafer can be reduced. Therefore, when the total oxidation capacity index is within the range, the polishing layer can be more conducive to achieving the target level of polishing performance.
[0180] In the polishing pad of the embodiment, the polishing process is performed when the polished surface and the slurry are in indirect or direct contact. Therefore, the metal component in the polishing layer improves the friction induction level of the polished surface and the adsorption / desorption ability and dispersion ability between the polished surface and the slurry, thereby becoming an important factor for improving the polishing performance of the polishing pad of the embodiment.
[0181] The electrical properties of the polishing layer of the polishing pad constituting one embodiment affect the degree of change in adsorption / desorption between the surface of the slurry particles and the polishing pad and the polishing performance. Specifically, the metal concentration in the polishing layer is one of the important factors that can change the electrical properties in the polishing layer. In order to objectively evaluate the degree of adsorption between the polishing layer and the slurry, the present invention aims to objectively evaluate the polishing performance of the polishing layer by introducing the concept of the total oxidation capacity index. Therefore, the total oxidation capacity index represents the degree of adsorption between the polishing layer and the slurry, and can be an indicator that can confirm the polishing rate and flattening performance level of the polishing pad through the degree of adsorption between the polishing layer and the slurry during the polishing process.
[0182] The metal may be added to the polishing layer. The metal may be added by selecting at least one of the group consisting of metal salts, metal particles, metal binders, and combinations thereof. For example, the metal salts, metal particles, or metal binders may be added to the polishing layer as independent additives, or may be added in a state of being mixed with other components constituting the polishing layer.
[0183] The metal may be added to the polishing layer in the form of a metal salt. For example, the metal or metal salt may include one selected from the group consisting of iron chloride, iron bromide, iron chloride anhydrous, iron oxide, iron acetate, aluminum chloride anhydrous, aluminum bromide, aluminum oxide, aluminum triacetate, zinc chloride, zinc bromide, zinc oxide, zinc acetate, and combinations thereof, but is not limited thereto.
[0184] In addition, the content of the metal can be adjusted to the range by addition. In addition, the metal can be added to the polishing layer through a reactor, a raw material supply line, a raw material or a surrounding environment. At this time, in this embodiment, the content of the metal can be appropriately adjusted to the range by various methods such as adding a metal salt.
[0185] In one embodiment, the polishing layer is dissolved using nitric acid and hydrochloric acid below pH 3, and then the dissolved product is pretreated at about 200° C. for about 16 hours and then measured by ICP-OES. The detected metal concentration is correlated with the hardness, electrical properties, and adsorption and desorption degree of the polishing layer with the slurry.
[0186] However, the technical purpose of the polishing pad of one embodiment is as follows: when the metal concentration in the polishing layer detected by ICP-OES measurement of the processing composition meets the conditions, the final polishing performance of the polishing pad can achieve a desired level. That is, within the scope of meeting this technical purpose, even if the type, content, process conditions, etc. of the monomers used are slightly different, it cannot be regarded as deviating from the scope of the purpose of the present invention.
[0187] The curing agent is a compound used to chemically react with the urethane prepolymer to form a final cured structure in the polishing layer, for example, it may include an amine compound or an alcohol compound. Specifically, the curing agent may include one selected from the group consisting of aromatic amines, aliphatic amines, aromatic alcohols, aliphatic alcohols, and combinations thereof.
[0188] For example, the curing agent may include 4,4'-methylenebis(2-chloroaniline) (MOCA), diethyltoluenediamine (DETDA), diaminodiphenylmethane, dimethylthio-toluene diamine (DMTDA), propanediol bis p-aminobenzoate, methylene bis-anthranilic acid methyl ester (Methylene One of the group consisting of bis(4-amino-3-chlorophenyl)methane and combinations thereof.
[0189] The content of the curing agent may be about 18 parts by weight to about 28 parts by weight, for example, about 19 parts by weight to about 27 parts by weight, for example, about 20 parts by weight to about 26 parts by weight, relative to 100 parts by weight of the preliminary composition. When the content of the curing agent satisfies the above range, it is more conducive to achieving the desired performance of the polishing pad.
[0190] In the case where the curing agent includes an amine compound, a molar ratio of isocyanate (NCO) groups in the preliminary composition to ammonia (NH2) groups in the curing agent may be about 1:0.60 to about 1:0.99, for example, about 1:0.60 to about 1:0.95, for example, about 1:0.60 or more and less than about 1:0.90.
[0191] The foaming agent is a component used to form the pore structure in the polishing layer, and may include one selected from the group consisting of a solid foaming agent, a gas foaming agent, a liquid foaming agent, and a combination thereof. In one embodiment, the foaming agent may include a solid foaming agent, a gas foaming agent, or a combination thereof.
[0192] The average particle size of the solid foaming agent may be about 5 μm to about 200 μm, for example, about 20 μm to about 50 μm, for example, about 21 μm to about 50 μm, for example, about 21 μm to about 40 μm. When the solid foaming agent is the thermally expanded particles described below, the average particle size of the solid foaming agent refers to the average particle size of the thermally expanded particles themselves, and when the solid foaming agent is the unexpanded particles to be described later, the average particle size of the solid foaming agent refers to the average particle size of the particles expanded by heat or pressure.
[0193] The solid foaming agent may include expandable particles. The expandable particles are particles having the property of being expandable by heat or pressure, and their final size in the polishing layer depends on the heat or pressure applied during the preparation of the polishing layer. The expandable particles may include heat-expanded particles, unexpanded particles, or a combination thereof. The heat-expanded particles are particles pre-expanded by heat, and refer to particles whose size changes little or almost do not change due to the heat or pressure applied during the preparation of the polishing layer. The unexpanded particles are particles that have not been pre-expanded, and refer to particles that are expanded by applying heat or pressure during the preparation of the polishing layer and whose final size is determined.
[0194] The expandable particles may include: an outer skin made of a resin material; and an expansion inducing component present inside the outer skin.
[0195] For example, the outer skin may include a thermoplastic resin, and the thermoplastic resin may be one or more selected from the group consisting of vinylidene chloride copolymers, acrylonitrile copolymers, methacrylonitrile copolymers, and acrylic copolymers.
[0196] The expansion inducing component may include one selected from the group consisting of hydrocarbon compounds, fluorine and chlorine compounds, tetraalkylsilane compounds, and combinations thereof.
[0197] Specifically, the hydrocarbon compound may include one selected from the group consisting of ethane, ethylene, propane, propene, n-butane, isobutane, n-butene, isobutene, n-pentane, isopentane, neopentane, n-hexane, heptane, petroleum ether, and combinations thereof.
[0198] The fluorine-chlorine compound may include one selected from the group consisting of trichlorofluoromethane (CCl3F), dichlorodifluoromethane (CCl2F2), chlorotrifluoromethane (CClF3), dichlorotetrafluoroethane (CClF2-CClF2) and combinations thereof.
[0199] The tetraalkylsilane compound may include one selected from the group consisting of tetramethylsilane, trimethylethylsilane, trimethylisopropylsilane, trimethyl-n-propylsilane, and combinations thereof.
[0200] The solid foaming agent may selectively contain inorganic component treated particles. For example, the solid foaming agent may contain expandable particles treated with inorganic components. In one embodiment, the solid foaming agent may contain expandable particles treated with silicon dioxide (SiO2) particles. The inorganic component treatment of the solid foaming agent may prevent aggregation between multiple particles. The chemical, electrical and / or physical properties of the foaming agent surface of the solid foaming agent treated with inorganic components may be different from those of the solid foaming agent not treated with inorganic components.
[0201] Based on 100 parts by weight of the urethane prepolymer, the content of the solid foaming agent can be about 0.5 parts by weight to about 10 parts by weight, for example, about 1 part by weight to about 3 parts by weight, for example, about 1.3 parts by weight to about 2.7 parts by weight, for example, about 1.3 parts by weight to about 2.6 parts by weight.
[0202] The type and content of the solid foaming agent can be designed according to the desired pore structure and physical properties of the polishing layer.
[0203] The gas foaming agent may include an inert gas and may be added during the reaction of the urethane prepolymer and the curing agent to serve as a pore forming element.
[0204] The type of the inert gas is not particularly limited, as long as it is a gas that does not participate in the reaction between the urethane prepolymer and the curing agent. For example, the inert gas may include one selected from the group consisting of nitrogen (N2), argon (Ar), helium (He), and a combination thereof. Specifically, the inert gas may include nitrogen (N2) or argon (Ar).
[0205] The type and content of the gas foaming agent can be designed according to the desired pore structure and physical properties of the polishing layer.
[0206] In one embodiment, the foaming agent may include a solid foaming agent. For example, the foaming agent may be formed only of a solid foaming agent.
[0207] The solid foaming agent may include expandable particles, and the expandable particles may include thermally expanded particles. For example, the solid foaming agent may consist only of thermally expanded particles. In the case where the solid foaming agent does not include the unexpanded particles but consists only of thermally expanded particles, although the variability of the pore structure decreases, the predictability increases, thereby facilitating uniform pore characteristics in all areas of the polishing layer.
[0208] In one embodiment, the thermally expanded particles may be particles having an average particle size of about 5 μm to about 200 μm. The average particle size of the thermally expanded particles may be about 5 μm to about 100 μm, for example, about 10 μm to about 80 μm, for example, about 20 μm to about 70 μm, for example, about 20 μm to about 50 μm, for example, about 30 μm to about 70 μm, for example, about 25 μm to 45 μm, for example, about 40 μm to about 70 μm, for example, about 40 μm to about 60 μm. The average particle size is defined as D50 of the thermally expanded particles.
[0209] In one embodiment, the density of the thermally expanded particles may be about 30 kg / m 3 About 80kg / m 3 , for example, about 35 kg / m 3 About 80kg / m 3 , for example, about 35 kg / m 3 About 75kg / m 3 , for example, about 38 kg / m 3 About 72kg / m 3 , for example, about 40kg / m 3 About 75kg / m 3 , for example, about 40kg / m 3 About 72kg / m 3 .
[0210] In one embodiment, the foaming agent may include a gas foaming agent. For example, the foaming agent may include a solid foaming agent and a gas foaming agent. Matters related to the solid foaming agent are as described above.
[0211] The gas blowing agent may include nitrogen.
[0212] The gas foaming agent can be injected using a specified injection line during the mixing of the urethane prepolymer, the solid foaming agent, and the curing agent. The injection speed of the gas foaming agent can be about 0.8 L / min to about 2.0 L / min, for example, about 0.8 L / min to about 1.8 L / min, for example, about 0.8 L / min to about 1.7 L / min, for example, about 1.0 L / min to about 2.0 L / min, for example, about 1.0 L / min to about 1.8 L / min, for example, about 1.0 L / min to about 1.7 L / min.
[0213] The composition for preparing the polishing layer may further include other additives such as surfactants, reaction rate regulators, etc. The names such as "surfactant", "reaction rate regulator", etc. are arbitrarily named based on the main effects of the corresponding substances, and the functions performed by each corresponding substance are not limited to the names of the substances.
[0214] The surfactant is not particularly limited as long as it can prevent pores from agglomerating or overlapping. For example, the surfactant may include a silicon-based surfactant.
[0215] Based on 100 parts by weight of the urethane prepolymer, the surfactant can be used in an amount of about 0.2 parts by weight to about 2 parts by weight. Specifically, relative to 100 parts by weight of the urethane prepolymer, the content of the surfactant can be about 0.2 parts by weight to about 1.9 parts by weight, for example, about 0.2 parts by weight to about 1.8 parts by weight, for example, about 0.2 parts by weight to about 1.7 parts by weight, for example, about 0.2 parts by weight to about 1.6 parts by weight, for example, about 0.2 parts by weight to about 1.5 parts by weight, for example, about 0.5 parts by weight to 1.5 parts by weight. In the case where the content of the surfactant is within the range, the pores caused by the gas foaming agent can be stably formed and maintained in the mold.
[0216] The reaction rate regulator is a regulator that plays a role in promoting or delaying the reaction. According to the purpose, a reaction accelerator, a reaction delayer, or both can be used. The reaction rate regulator can include a reaction accelerator. For example, the reaction accelerator can be one or more reaction accelerators selected from the group consisting of tertiary amine compounds and organometallic compounds.
[0217] Specifically, the reaction rate regulator may include a selected from triethylenediamine, dimethylethanolamine, tetramethylbutylenediamine, 2-methyl-triethylenediamine, dimethylcyclohexylamine, triethylamine, triisopropanolamine, 1,4-diazabicyclo (2,2,2) octane, bis (2-methylaminoethyl) ether, trimethylaminoethylethanolamine, N,N,N,N,N "-pentamethyldiethylenetriamine, dimethylaminoethylamine, dimethylaminopropylamine, benzyldimethylamine, N-ethyl The reaction rate regulator may include at least one selected from the group consisting of morpholine, N,N-dimethylaminoethylmorpholine, N,N-dimethylcyclohexylamine, 2-methyl-2-azanorbornane, dibutyltin dilaurate, stannous octoate, dibutyltin diacetate, dioctyltin diacetate, dibutyltin maleate, dibutyltin diisooctoate and dibutyltin dithiol. Specifically, the reaction rate regulator may include at least one selected from the group consisting of benzyldimethylamine, N,N-dimethylcyclohexylamine and triethylamine.
[0218] Based on 100 parts by weight of the urethane prepolymer, the amount of the reaction rate regulator can be about 0.05 parts by weight to about 2 parts by weight. Specifically, based on 100 parts by weight of the urethane prepolymer, the amount of the reaction rate regulator can be about 0.05 parts by weight to about 1.8 parts by weight, for example, about 0.05 parts by weight to about 1.7 parts by weight, for example, about 0.05 parts by weight to about 1.6 parts by weight, for example, about 0.1 parts by weight to about 1.5 parts by weight, for example, about 0.1 parts by weight to about 0.3 parts by weight, for example, about 0.2 parts by weight to about 1.8 parts by weight, for example, about 0.2 parts by weight to about 1.7 parts by weight, for example, about 0.2 parts by weight to about 1.6 parts by weight, for example, about 0.2 parts by weight to about 1.5 parts by weight, for example, about 0.5 parts by weight to about 1 part by weight. When the reaction rate regulator is used within the above content range, the curing reaction rate of the preliminary composition can be appropriately adjusted, thereby forming a polishing layer having pores of a desired size and hardness.
[0219] In the case where the polishing pad includes a buffer layer, the buffer layer plays a role of supporting the polishing layer and absorbing and dispersing external impact applied to the polishing layer, thereby minimizing damage to a polishing object and occurrence of defects in a polishing process using the polishing pad.
[0220] The buffer layer may include non-woven fabric or suede, but is not limited thereto.
[0221] In one embodiment, the buffer layer may be a non-woven fabric impregnated with resin. The non-woven fabric may include one selected from the group consisting of polyester fiber, polyamide fiber, polypropylene fiber, polyethylene fiber and a combination thereof.
[0222] The resin impregnated in the nonwoven fabric may include one selected from the group consisting of polyurethane resin, polybutadiene resin, styrene-butadiene copolymer resin, styrene-butadiene-styrene copolymer resin, acrylonitrile-butadiene copolymer resin, styrene-ethylene-butadiene-styrene copolymer resin, silicone rubber resin, polyester elastomer resin, polyamide elastomer resin and combinations thereof.
[0223] In the polishing pad of an embodiment, the hardness of the polishing surface of the polishing layer may be about 80 Shore D or less, for example, 30 Shore D to 80 Shore D. Specifically, the hardness of the polishing layer may be 40 Shore D to 80 Shore D, 50 Shore D to 80 Shore D, 40 Shore D to 70 Shore D, 50 Shore D to 70 Shore D, or 55 Shore D to 65 Shore D, but is not limited thereto.
[0224] The tensile strength of the polishing layer may be less than about 25 N / mm 2 , for example, can be about 10 N / mm 2 Above and less than about 25N / mm 2 , for example, can be about 15N / mm 2 To about 25N / mm 2 . The elongation of the polishing layer may be about 100% or more, for example, about 100% to about 200%. The cutting rate of the polishing layer may be about 10 μm / hr or more, for example, about 10 μm / hr to about 80 μm / hr, for example, about 15 μm / hr to about 50 μm / hr. For example, when the hardness of the polishing surface, the tensile strength and elongation of the polishing layer, and the cutting rate of the polishing layer are all within the range, it can be evaluated that the processing composition presents physical and mechanical properties corresponding to the peak characteristics. In this case, the polishing pad including the polishing layer can achieve excellent polishing performance when used in a semiconductor device process.
[0225] Hereinafter, a method for preparing the polishing pad will be described.
[0226] In another embodiment of the present invention, a method for preparing a polishing pad may be provided, the method comprising the following steps: preparing a preliminary composition comprising a prepolymer; mixing zinc into the preliminary composition; preparing a composition for preparing a polishing layer comprising the preliminary composition, a foaming agent and a curing agent; and preparing a polishing layer having a zinc concentration of about 0.5 ppm to about 40 ppm by weight based on the total weight by curing the composition for preparing the polishing layer.
[0227] The step of preparing the preliminary composition may be a step of preparing a urethane prepolymer by reacting a diisocyanate compound with a polyol compound. Matters regarding the diisocyanate compound and the polyol compound are the same as those described above regarding the polishing pad.
[0228] The isocyanate group content (NCO%) of the preliminary composition may be about 5 wt % to about 11 wt %, for example, about 5 wt % to about 10 wt %, for example, about 6 wt % to about 9.5 wt %. In this case, it is more advantageous to prepare a polishing layer having the chemical bonding structure. The isocyanate group content of the preliminary composition may be derived from the terminal isocyanate group of the urethane prepolymer, the unreacted isocyanate group in the diisocyanate compound, and the like.
[0229] The viscosity of the preparatory composition at about 80° C. may be about 100 cps to about 1000 cps, for example, about 200 cps to about 800 cps, for example, about 200 cps to about 600 cps, for example, about 200 cps to about 600 cps, for example, about 300 cps to about 600 cps.
[0230] The foaming agent may include a solid foaming agent or a gas foaming agent. The type of the foaming agent and other related matters are the same as the above description of the polishing pad.
[0231] In the case where the foaming agent includes a solid foaming agent, the step of preparing the composition for preparing the polishing layer may include the steps of: preparing a first preliminary composition by mixing the preliminary composition with the solid foaming agent; and preparing a second preliminary composition by mixing the first preliminary composition with a curing agent.
[0232] The first preparatory composition may have a viscosity of about 1000 cps to about 2000 cps at about 80° C., for example, about 1000 cps to about 1800 cps, for example, about 1000 cps to about 1600 cps, for example, about 1500 cps to about 2000 cps.
[0233] In the case where the foaming agent includes a gas foaming agent, the step of preparing the composition for preparing the polishing layer may include the following steps: preparing a third preliminary composition including the preliminary composition and the curing agent; and preparing a fourth preliminary composition by injecting the gas foaming agent into the third preliminary composition.
[0234] In one embodiment, the third preliminary composition may further include a solid foaming agent.
[0235] The metal concentration of the polishing pad of the example can be adjusted to the above range by the following method.
[0236] The zinc content in the polishing layer can be adjusted by adding the zinc component as described above to the preliminary composition in an appropriate content. That is, the zinc content in the polishing layer can be adjusted to be within the above range by appropriately adding the zinc component to the preliminary composition. The zinc added to the preliminary composition can be added in the form of metal particles, metal ions or metal salts.
[0237] In one embodiment, the step of further mixing aluminum and iron with zinc in the preliminary composition may be included. The metal component may be added in the form of metal particles, metal ions or metal salts. In addition, the above description of the polishing pad is applicable to the concentration range of each metal in the polishing layer.
[0238] In the polishing pad prepared by the preparation method, the polishing layer is as described above, and the total oxidation ability index represented by the third formula can be about 1.5 to about 10, for example, about 2 to about 9, for example, about 2 to about 8, for example, about 3 to about 7, for example, about 2 to about 7.
[0239] In one embodiment, the process for preparing the polishing layer may include the following steps: preparing a mold preheated to a first temperature; injecting the polishing layer preparation composition into the preheated mold and curing the polishing layer preparation composition; and post-curing the cured polishing layer preparation composition under a second temperature condition higher than the preheating temperature.
[0240] In one embodiment, the temperature difference between the first temperature and the second temperature may be about 10°C to about 40°C, for example, about 10°C to about 35°C, for example, about 15°C to about 35°C.
[0241] In one embodiment, the first temperature may be about 60°C to about 100°C, for example, about 65°C to about 95°C, for example, about 70°C to about 90°C.
[0242] In one embodiment, the second temperature may be about 100°C to about 130°C, for example, about 100°C to 125°C, for example, about 100°C to about 120°C.
[0243] The step of curing the polishing layer preparation composition at the first temperature can be performed for about 5 minutes to about 60 minutes, for example, about 5 minutes to about 40 minutes, for example, about 5 minutes to about 30 minutes, for example, about 5 minutes to about 25 minutes.
[0244] The step of post-curing the polishing layer preparation composition cured at the first temperature at the second temperature can be performed for about 5 hours to about 30 hours, for example, about 5 hours to about 25 hours, for example, about 10 hours to about 30 hours, for example, about 10 hours to about 25 hours, for example, about 12 hours to about 24 hours, for example, about 15 hours to about 24 hours.
[0245] The method for preparing the polishing pad may include the step of processing at least one surface of the polishing layer.
[0246] The step of processing at least one surface of the polishing layer may include at least one of the following steps: a first step of forming grooves on at least one surface of the polishing layer; a second step of performing line turning on at least one surface of the polishing layer; and a third step of roughening at least one surface of the polishing layer.
[0247] In the first step, the grooves may include at least one of: concentric circular grooves formed at regular intervals from the center of the polishing layer; and radial grooves continuously connected from the center of the polishing layer to the edge of the polishing layer.
[0248] In the second step, the turning process may be performed by cutting the polishing layer to a predetermined thickness using a cutting tool.
[0249] In the third step, the roughening treatment may be performed by processing the surface of the polishing layer using a sanding roller.
[0250] The method for preparing the polishing pad may further include the step of laminating a buffer layer on the opposite surface of the polishing surface of the polishing layer. Matters regarding the buffer layer are the same as those described above regarding the polishing pad.
[0251] The polishing layer and the buffer layer may be laminated using a hot melt adhesive as a medium.
[0252] The hot melt adhesive is coated on the opposite surface of the polishing surface of the polishing layer, and the hot melt adhesive is coated on the surface of the buffer layer in contact with the polishing layer, and after the polishing layer and the buffer layer are stacked so that the surfaces coated with the hot melt adhesive are in contact, the two layers can be welded using a pressure roller.
[0253] In another embodiment of the present invention, a method for preparing a semiconductor device is provided, comprising the following steps: providing a polishing pad comprising a polishing layer, and bringing a polishing surface of the polishing layer into contact with a polished surface of a polishing object, and then relatively rotating the polishing layer and the polishing object to polish the polishing object; the polishing object comprises a semiconductor substrate, the polishing layer comprises zinc, and the concentration of the zinc is about 0.5 ppm to about 40 ppm by weight based on the total weight of the polishing layer.
[0254] The matters concerning the polishing pad described above can all be applied to matters concerning the structure and composition of the polishing layer, the processing composition of the polishing layer, and the concentrations of zinc, aluminum, and iron in the polishing layer. By using a polishing pad including a polishing layer having the above characteristics in the method for manufacturing a semiconductor device, the semiconductor device manufactured thereby can exhibit excellent functions derived from the excellent polishing results of the semiconductor substrate.
[0255] In the method for manufacturing the semiconductor device, the polishing layer is as described above, and the total oxidation ability index represented by the third formula may be about 1.5 to about 10, for example, about 2 to about 9, for example, about 2 to about 8, for example, about 3 to about 7, for example, about 2 to about 7. The polishing layer having the total oxidation ability index within the range is applied to the method for manufacturing the semiconductor device, so that the polished surface of the semiconductor substrate can be polished with excellent polishing efficiency, and excellent polishing performance can be achieved in terms of polishing flatness and defect prevention.
[0256] Figure 2 Schematic diagram schematically showing a method for manufacturing a semiconductor device according to an embodiment. Figure 2 In the step of providing the polishing pad including the polishing layer, the polishing pad 110 may be disposed on a plate 120 .
[0257] The polishing object may include a semiconductor substrate, and the semiconductor substrate 130 may be arranged such that its polished surface contacts the polishing surface of the polishing layer of the polishing pad 110. At this time, the polished surface of the semiconductor substrate 130 may contact the polishing surface of the polishing layer directly or indirectly via a fluid slurry or the like.
[0258] In one embodiment, the method for manufacturing a semiconductor device may further include the step of supplying polishing slurry 150 onto the polishing surface of the polishing layer of the polishing pad 110. For example, the polishing slurry 150 may be supplied onto the polishing surface through a supply nozzle 140.
[0259] The flow rate of the polishing slurry 150 sprayed through the supply nozzle 140 may be about 10 ml / min to about 1000 ml / min, for example, about 10 ml / min to about 800 ml / min, for example, about 50 ml / min to about 500 ml / min, but is not limited thereto.
[0260] The polishing slurry 150 may include silicon dioxide slurry or ceria slurry. When the polishing slurry includes silicon dioxide particles or ceria particles as polishing particles and the zinc concentration of the polishing layer satisfies the above range, the polishing particles can be desorbed and adsorbed on the polishing surface with appropriate bonding force through appropriate electrical interaction between the polishing slurry and the polishing surface of the polishing layer, and as a result, it is possible to help ensure the best polishing rate in terms of polishing efficiency while maximizing the defect prevention effect.
[0261] Specifically, when the polishing slurry contains silica particles or ceria particles as polishing particles and the total oxidation ability index of the polishing layer according to the third formula satisfies the range, the electrical interaction and chemical interaction between the polishing slurry and the polishing surface of the polishing layer can be further improved in ensuring the polishing rate and defect prevention effect at the target level.
[0262] The semiconductor substrate 130 mounted on the polishing head 160 can be pressed with a specified load to make the semiconductor substrate contact with the polishing surface. The load by which the polishing head 160 presses the polished surface of the semiconductor substrate 130 onto the polishing surface can be selected, for example, in the range of about 0.01 psi to about 20 psi according to the purpose, for example, can be selected in the range of about 0.1 psi to about 15 psi, but is not limited thereto. When the polishing surface of the polishing layer and the polished surface of the semiconductor substrate contact each other under the action of the load, the polishing layer exhibits the hardness and elongation represented by the peak characteristics, and the corresponding elasticity and contact area can be provided to the polished surface of the semiconductor substrate, thereby facilitating the polishing rate and defect prevention effect of the semiconductor substrate to reach the target level.
[0263] The semiconductor substrate 130 and the polishing pad 110 can rotate relative to each other in a state where the respective polished surfaces and polishing surfaces are in contact with each other. At this time, the rotation direction of the semiconductor substrate 130 and the rotation direction of the polishing pad 110 can be the same or opposite. The rotation speeds of the semiconductor substrate 130 and the polishing pad 110 can be selected in the range of about 10 rpm to about 500 rpm according to the purpose, for example, the range can be about 30 rpm to about 200 rpm, but is not limited thereto. When the rotation speeds of the semiconductor substrate and the polishing pad respectively meet the range, the polishing layer exhibits the hardness and elongation represented by the peak characteristics, and the corresponding elasticity and contact area can be provided to the polished surface of the semiconductor substrate, thereby facilitating the polishing rate and defect prevention effect of the semiconductor substrate to reach the target level.
[0264] In one embodiment, in order to keep the polishing surface of the polishing pad 110 in a state suitable for polishing, the method for preparing the semiconductor device may further include a step of processing the polishing surface of the polishing pad 110 by a dresser 170 while polishing the semiconductor substrate 130 .
[0265] In one embodiment, in the method for preparing the semiconductor device, the semiconductor substrate comprises a silicon dioxide film, the polished surface is the surface of the silicon dioxide film, the number of surface defects on the polished surface after polishing is less than 5, and the average polishing rate of the silicon dioxide film can be to For example, about More than and less than about
[0266] In the method for manufacturing the semiconductor device, the polishing pad including the polishing layer having the above characteristics is used, and a semiconductor substrate having a silicon dioxide film is used as a polishing object, so that the above polishing rate and defect prevention performance can be achieved.
[0267] Since the polishing pad includes a polishing layer corresponding to the metal concentration exhibited by the processing composition treated with the polishing pad under prescribed conditions, the polishing surface of the polishing layer can exhibit appropriate hardness and electrical characteristics.
[0268] Therefore, the polishing pad can present a polishing rate and a polishing flatness within a target range in polishing the polishing object. In addition, since the polishing pad contains an appropriate amount of the metal, the degree of adsorption of the polishing pad to the slurry is increased during the polishing process, and the polishing pad can have an improved polishing rate and polishing performance.
[0269] The method for manufacturing a semiconductor device using the polishing pad can achieve high process efficiency in polishing a semiconductor substrate as a polishing object. In addition, the method for manufacturing a semiconductor device of an embodiment can make the polished surface of the semiconductor substrate have high polishing flatness and minimal defects.
[0270] In addition, since the polishing pad of the embodiment contains the metal component, the electrical characteristics of the polishing surface can be appropriately adjusted. For example, since the polishing layer contains the metal component, the surface-modified polishing particles can be easily bonded to the polishing surface by electrostatic attraction.
[0271] In particular, the surface potential of the polishing surface can be adjusted according to the metal composition so that the polishing particles with surface modification are bound to the polishing surface by appropriate attraction.
[0272] Since the metal component has the total oxidation ability index as described above, the surface-modified polishing particles can be bonded to the polishing surface through appropriate electrostatic attraction.
[0273] Therefore, a proper amount of polishing particles can remain near the polishing surface under the action of appropriate bonding force. Therefore, a semiconductor substrate such as a semiconductor wafer can be effectively polished by the polishing surface and the polishing particles.
[0274] Specific examples of the present invention are given below. However, the examples described below are only used to specifically illustrate or describe the present invention, and are not used to limit the present invention.
[0275] <Examples and Comparative Examples>
[0276] Example 1
[0277] With respect to 100 parts by weight of the total weight of the diisocyanate component, TDI and H were mixed in the relative weight ratios shown in Table 1. 12 MDI. PTMG and DEG were mixed in the relative weight ratios shown in Table 1 below, respectively, with respect to 100 parts by weight of the total weight of the polyol component. A mixed raw material was prepared by mixing a total of 100 parts by weight of diisocyanate and a total of 220 parts by weight of polyol with each other. A preliminary composition containing a urethane prepolymer was prepared by adding the mixed raw material to a four-necked flask and reacting it at 80° C. The isocyanate group (NCO group) content in the preliminary composition was adjusted to 9% by weight.
[0278] A solid foaming agent (Nouryon) as expandable particles was mixed into the preliminary composition at 1.0 parts by weight. In addition, zinc acetate (Zn(CH3CO2)2), iron acetate (Fe(C2H3O2)2) and aluminum acetate (Al(CH3CO2)3) were added in the parts by weight shown in Table 1 relative to 100 parts by weight of the total weight of the preliminary composition. At this time, the zinc acetate, iron acetate and aluminum acetate were diluted with acetone and added to the preliminary composition.
[0279] 4,4′-methylenebis(2-chloroaniline) (MOCA) was mixed into the preliminary composition as a curing agent so that the molar ratio of NH 2 groups of the MOCA to NCO groups in the preliminary composition was 0.95.
[0280] The preliminary composition was injected at a discharge rate of 10 kg / min into a mold having a width of 1000 mm, a length of 1000 mm, and a height of 3 mm and preheated to 90° C. Then, the preliminary composition was post-cured at a temperature of 110° C. to prepare a polishing layer.
[0281] Example 2 and Example 3
[0282] A polishing layer was prepared in the same manner as in Example 1 except that the input amounts of zinc acetate, iron acetate, and aluminum acetate were changed as shown in Table 1 below.
[0283] Comparative Example 1
[0284] With respect to 100 parts by weight of the total weight of the diisocyanate component, TDI and H were mixed in the relative weight ratios shown in Table 1. 12 MDI. PTMG and DEG were mixed in the relative weight ratios shown in Table 1 below, respectively, with respect to 100 parts by weight of the total weight of the polyol component. A mixed raw material was prepared by mixing a total of 100 parts by weight of diisocyanate and a total of 220 parts by weight of polyol with each other. A preliminary composition containing a urethane prepolymer was prepared by adding the mixed raw material to a four-necked flask and reacting it at 80° C. The isocyanate group (NCO group) content in the preliminary composition was adjusted to 9% by weight.
[0285] 1.0 part by weight of a solid foaming agent (Nouryon) as expandable particles was mixed into the preliminary composition. In addition, zinc acetate, iron acetate, and aluminum acetate were added in the parts by weight shown in Table 1 relative to 100 parts by weight of the total weight of the preliminary composition. At this time, the zinc acetate, iron acetate, and aluminum acetate were diluted with acetone and added to the preliminary composition.
[0286] 4,4′-methylenebis(2-chloroaniline) (MOCA) was mixed into the preliminary composition as a curing agent, however, the molar ratio of the NH 2 group of the MOCA to the NCO group in the preliminary composition was 0.95.
[0287] The preliminary composition was injected into a mold having a width of 1000 mm, a length of 1000 mm, and a height of 3 mm and preheated to 90° C. at a discharge rate of 10 kg / min. At the same time, nitrogen (N2) was injected as a gas foaming agent at an injection rate of 1.0 L / min until the injection of the preliminary composition was completed. The preliminary composition was then subjected to a post-curing reaction at a temperature of 110° C. to prepare a polishing layer.
[0288] Comparative Example 2
[0289] A polishing layer was prepared in the same manner as in Comparative Example 1 except that the input amounts of zinc acetate, iron acetate, and aluminum acetate were changed as shown in Table 1 below.
[0290] After the polishing layers of Examples 1 to 3 and Comparative Examples 1 to 2 were processed to a thickness of 2 mm, concentric circular grooves 13 were formed on the polishing surfaces (see Figure 1A and Figure 1B ). Next, a buffer layer having a structure in which a polyester resin nonwoven fabric is impregnated with a urethane resin and having a thickness of 1.1 mm was prepared, and then a hot melt adhesive was applied to the opposite side of the polishing surface and the attachment surface of the buffer layer, and then laminated using a pressure roller. Thus, a final polishing pad was prepared.
[0291] [Table 1]
[0292]
[0293]
[0294] <Evaluation>
[0295] Experimental Example 1: ICP-OES measurement of processing composition
[0296] For each polishing layer of Examples 1 to 3 and Comparative Examples 1 to 2, x g (at this time, the sampling weight is less than 1 g) was randomly sampled from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness, and then 1 ml of nitric acid and 3 ml of hydrochloric acid were added to perform pretreatment with a graphite block at a temperature of 200° C. for 16 hours, and then measured by ICP-OES. At this time, ICP-OES used Agilent 5100, and its measurement conditions were as follows.
[0297] <Measurement conditions>
[0298] RF power: 1.2KW
[0299] Nebulizer flow: 0.7L / min
[0300] Plasma flow: 12L / min
[0301] Aux flow: 1L / min
[0302] Read time: 5s
[0303] The concentrations of zinc, aluminum and iron in the polishing layers of Examples 1 to 3 and Comparative Examples 1 to 2 are the average values of 5 measurements, expressed in parts by weight based on the total weight of the polishing layer, as shown in Table 2 below.
[0304] In addition, as described in the following Table 2, the value of the third formula is derived as the total oxidation ability index of each polishing layer of Examples 1 to 3 and Comparative Examples 1 and 2.
[0305] Experimental Example 2: Physical Property Evaluation of Polishing Layer or Polishing Pad
[0306] (1) Hardness
[0307] Each polishing layer of Examples 1 to 3 and Comparative Examples 1 to 2 was processed to a thickness of 2 mm, and then cut into a size of 5 cm×5 cm in length and width to prepare a sample. The sample was stored at 25° C. for 12 hours, and then the Shore D hardness was measured using a hardness tester.
[0308] (2) Tensile strength
[0309] After each polishing layer of Examples 1 to 3 and Comparative Examples 1 to 2 was processed to a thickness of 2 mm, a sample was prepared by cutting into a size of 4 cm×1 cm in length and width. The maximum strength value before the sample was broken was measured at a speed of 500 mm / min using a universal testing machine (UTM).
[0310] (3) Elongation
[0311] After each polishing layer of Examples 1 to 3 and Comparative Examples 1 to 2 was processed to a thickness of 2 mm, a sample was prepared by cutting into a size of 4 cm×1 cm in length and width. The maximum deformation length before the sample was broken was measured at a speed of 500 mm / min using a universal testing machine (UTM), and the ratio of the maximum deformation length to the initial length was then shown in the form of percentage (%).
[0312] (4) Cutting rate
[0313] For each polishing pad prepared using the polishing layers of Examples 1 to 3 and Comparative Examples 1 to 2 according to the above method, after pre-conditioning the polishing pad with deionized water for 10 minutes, the polishing pad was conditioned by spraying deionized water for 1 hour. The thickness change during the conditioning process was measured, and the thickness change (μm / hr) was calculated as the cutting rate of the polishing pad. The equipment used for conditioning was AP-300HM of CTS, the conditioning pressure was 6 lbf, the rotation speed was 100 to 110 rpm, and the disc used for conditioning was CI-45 of Saesol.
[0314] Experimental Example 3: Polishing Performance Evaluation
[0315] After preparing polishing pads using the polishing layers of Examples 1 to 3 and Comparative Examples 1 to 2, the polishing performance was evaluated as described below.
[0316] Silicon dioxide is deposited on a silicon wafer with a diameter of 300 mm by chemical vapor deposition (CVD) technology. The polishing pad is attached to a CMP machine and is set so that the surface of the silicon dioxide layer of the silicon wafer faces the polishing surface of the polishing pad. The calcined cerium dioxide slurry is supplied to the polishing pad at a speed of 250 ml / min, while the silicon wafer is pressed onto the polishing surface with a load of 4.0 psi, and the silicon dioxide film is polished for 60 seconds by setting the rotation speed of the polishing pad and the silicon wafer to 150 rpm respectively. After polishing, the silicon wafer is removed from the carrier and mounted on a spin dryer, then washed with distilled water and dried with nitrogen for 15 seconds.
[0317] (1) Average polishing rate
[0318] The film thickness change of the dried silicon wafer before and after polishing was measured using an optical interferometer thickness gauge (SI-F80R, Kyence). The polishing rate was then calculated using the following formula. The polishing rate was measured 5 times in total and the average value was calculated, and the average value was used as the average polishing rate.
[0319]
[0320] (2) Defects
[0321] Polishing was performed in the same manner as the polishing rate measurement method, and the number of defects such as scratches was counted by visually observing the polished surface of the polished object. Specifically, after polishing, the silicon wafer was moved to a cleaner and washed for 10 seconds using 1% hydrogen fluoride (HF) and pure water (DIW), and 1% nitric acid (H2NO3) and pure water (DIW). Then, the silicon wafer was moved to a rotary dryer, washed with pure water (DIW), and dried with nitrogen (N2) for 15 seconds. Then, a defect detection device (Tenkor, XP+) was used to visually observe the changes in defects before and after polishing of the dried silicon wafer.
[0322] The results of Experimental Examples 1 to 3 are shown in Table 2 below.
[0323] [Table 2]
[0324]
[0325] Referring to Table 2, the polishing pad using the polishing layer of Examples 1 to 3 can confirm that the polishing result of the semiconductor substrate is very excellent based on its corresponding hardness, tensile strength, elongation, cutting rate and other properties, wherein in the processing composition for treating the above-mentioned polishing layer under specified conditions, the concentration of zinc in the polishing layer is 0.5ppm to 40ppm based on the total weight of the polishing layer, the concentration of iron in the polishing layer is 1ppm to 50ppm based on the total weight of the polishing layer, and the concentration of aluminum in the polishing layer is 2ppm to 50ppm based on the total weight of the polishing layer.
[0326] On the contrary, for the polishing layers of Comparative Examples 1 and 2, since the sum of the concentrations of iron, aluminum, and zinc based on the total weight of the polishing layers is outside the range of 5ppm to 40ppm, and the total oxidation ability index is outside the range of 1.5 to 10, it can be confirmed that their hardness is lower or higher than that of the polishing layers of Examples 1 to 3.
[0327] More specifically, in the case of Comparative Example 1, it was confirmed that since the total oxidation ability index was less than 1.5, the polarity was low, and the electrostatic repulsion between the polished surface and the slurry was reduced, resulting in a decrease in the polishing rate. In contrast, in the case of Comparative Example 2, it was confirmed that although the polishing rate was high, the electrostatic attraction between the polishing pad and the polished surface was strong, so the defects of the polished surface increased. Therefore, it was confirmed that the polishing pads of Comparative Examples 1 and 2 could not provide the intended level of polishing performance, and were inferior in terms of the defect of the average polishing rate.
Claims
1. A polishing pad, wherein: include: Polishing layer, The polishing layer comprises zinc, The concentration of zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer. The total concentration of iron, zinc and aluminum contained in the polishing layer from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness is 8 ppm to 30 ppm by weight based on the total weight of the polishing layer. The total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10, Form 3: Total oxidative capacity index = (Conv .Al ×Oxi .Al )+(Con .Zn× Oxi .Zn) +(Con .Fe ×Oxi .Fe ) In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer, Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
2. The polishing pad according to claim 1, wherein The concentration of iron is 1 ppm to 50 ppm by weight based on the total weight of the polishing layer.
3. The polishing pad according to claim 2, wherein: The concentration of aluminum is 2 ppm to 50 ppm by weight based on the total weight of the polishing layer.
4. The polishing pad according to claim 1, wherein: The hardness of the polishing layer is 53 to 60 Shore D, The polishing layer has an elongation of 80 to 110%.
5. A method for preparing a polishing pad, wherein: The steps include: preparing a preliminary composition comprising a prepolymer; mixing zinc into the preparatory composition; preparing a composition for preparing a polishing layer comprising the preliminary composition, a foaming agent and a curing agent; and A polishing layer is prepared by curing the composition for preparing a polishing layer, wherein the concentration of zinc in the polishing layer is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer, The total concentration of iron, zinc and aluminum contained in the polishing layer from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness is 8 ppm to 30 ppm by weight based on the total weight of the polishing layer. The total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10, Form 3: Total oxidizing capacity index = (Con .Al ×Oxi .Al )+(Con .Zn ×Oxi .Zn )+(Con. Fe ×Oxi .Fe ) In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer, Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
6. The method for preparing a polishing pad according to claim 5, wherein: The prepolymer comprises an isocyanate compound, The isocyanate compound includes any one of an aromatic diisocyanate compound and an alicyclic diisocyanate compound, The content of isocyanate groups in the prepolymer is 6 to 12 wt %.
7. A method for preparing a semiconductor device, wherein: The steps include: A polishing pad including a polishing layer is provided, and The polishing surface of the polishing layer is brought into contact with the polished surface of the polishing object, and then the polishing layer and the polishing object are relatively rotated to polish the polishing object; The polishing object comprises a semiconductor substrate, The polishing layer comprises zinc, The concentration of zinc is 0.5 ppm to 40 ppm by weight based on the total weight of the polishing layer. The total concentration of iron, zinc and aluminum contained in the polishing layer from the polishing surface of the polishing layer to a depth of 1 / 2 of the entire thickness is 8 ppm to 30 ppm by weight based on the total weight of the polishing layer. The total oxidation ability index of the polishing layer represented by the following formula 3 is 1.5 to 10, Form 3: Total oxidizing capacity index = (Con .Al ×Oxi .Al )+(Con .Zn ×Oxi .Zn )+(Con .Fe ×Oxi .Fe ) In the third formula, Con. Al is the ppm concentration value of aluminum weight based on the total weight of the polishing layer, the Con. Zn is the ppm concentration value of zinc weight based on the total weight of the polishing layer, the Con. Fe is the concentration value in ppm by weight of iron based on the total weight of the polishing layer, Said Oxi. Al is the ionization index of the aluminum, which is a value obtained by dividing the reciprocal of the primary ionization energy of the aluminum by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, Said Oxi. Zn is the ionization index of the zinc, which is the value obtained by dividing the reciprocal of the primary ionization energy of the zinc by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron, Said Oxi. Fe is the ionization index of the iron, which is a value obtained by dividing the reciprocal of the primary ionization energy of the iron by the sum of the reciprocal of the primary ionization energy of the aluminum, the reciprocal of the primary ionization energy of the zinc, and the reciprocal of the primary ionization energy of the iron.
